Thermal Regeneration and Reuse of Carbon and Glass Fibers from Waste Composites - Alexey V. Nistratov; Natalya N. Klimenko; Igor V. Pustynnikov; Long Kim Vu (Ital Publication, 2022)
This article aims to develop a method for regenerating and reusing carbon and glass fibers extracted from unrecyclable scraps of carbon plastics, printer parts, and laminating coating. A comparison of known methods of fiber regeneration revealed the advantages of thermal treatment: absence of costs of reagents and complex equipment; better preservation of composition; and strength of fibers. Based on the results of thermographic analysis of wastes in nitrogen and air, the destruction temperatures of their organic matrices were determined (200-460°С), and the use of calcination instead of pyrolysis was justified. The appearance and surface quality of the regenerated fibers are characterized by optical and electron microscopy. It has been established that quantitative extraction of pure carbon and glass fibers from waste crushed to 1 cm is efficient by their calcination at 700 °C for 0.5 h and 500 °C for 1 h, respectively. The principle of creating new composites with the obtained fibers based on the similarity of their composition and binding materials (matrices) has been proposed. It was shown that the introduction of 1 wt% of fibers into slag blocks and active carbon pellets considerably increases their compressive strength, but the bending strength does not change due to dispersed reinforcement. Possible improvement of mechanical properties of products requires reagent treatment of the fiber surface or the introduction of binder additives. Calculations show that the developed method of recycling composite waste can produce 2.3 tons/hour of reinforced building materials that are good for the environment and the economy, excluding expenses for landfill waste disposal and reducing the cost of the product by replacing the primary fiber for the secondary one. Doi: 10.28991/ESJ-2022-06-05-04 Full Text: PDF